Pioneering New Approaches in Support of Sustainable Development in the Extractive Sector : Guidelines for Sustainable Development Assessments - Chown, Davin; Hoffman, Belynda (World Bank, Washington, DC, 2014)
These Guidelines attempt to expand on social impact assessments (SIAs) and other assessment tools, such as environmental impact assessments (EIAs) and macro-economic planning processes conducted by government (local economic development planning), to develop a more comprehensive set of guidelines that examine positive impacts as well as opportunities for enhancing socio-economic development around the proposed development. The resulting assessment contributes to the development of social plans or community development plans.